Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3109/00365513.2011.598944
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between inflammation, endothelial dysfunction and proteinuria in patients with diabetic nephropathy

Abstract: TNF-α, IL-6, hsCRP and urinary protein concentrations are higher in the DN patients. There were no correlations among pro-inflammatory cytokines concentrations and markers of vascular endotelial disfunction. These findings did not show vascular endothelial dysfunction, but may indicate glomerular endothelial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 36 publications
2
33
1
Order By: Relevance
“…In lammation induced by endothelial dysfunction plays an important role in the development of albuminuria in diabetic patients [8], however, for the irst time, the current study demonstrated a signi icant relationship between the BH4/BH2 ratios (but not biopterin levels) with albuminuria. As this ratio includes information about the levels of both biopterins, may be a more sensitive and reliable marker of endothelial dysfunction and glomerular injury than the isolate values of BH4 or BH2 [9].…”
Section: Discussioncontrasting
confidence: 58%
“…In lammation induced by endothelial dysfunction plays an important role in the development of albuminuria in diabetic patients [8], however, for the irst time, the current study demonstrated a signi icant relationship between the BH4/BH2 ratios (but not biopterin levels) with albuminuria. As this ratio includes information about the levels of both biopterins, may be a more sensitive and reliable marker of endothelial dysfunction and glomerular injury than the isolate values of BH4 or BH2 [9].…”
Section: Discussioncontrasting
confidence: 58%
“…It determines the degree of endothelial dysfunction on the basis of NO production capacity of the brachial artery. There are reports in the literature showing decreased FMD in patients with diabetic nephropathy (16).…”
Section: Introductionmentioning
confidence: 99%
“…6 Interleukin-6 (IL-6) and C-reactive protein (CRP), 2 sensitive physiologic markers of subclinical systemic inflammation, have been shown to be associated with hyperglycemia, endothelial dysfunction, and microvascular complications in patients with T2DM. 7,8 Further, these 2 inflammatory markers have been shown to initiate coagulation at several points in primary and secondary hemostatic systems. 9,10 Therefore, we speculated that plasma CRP and IL-6 concentrations might serve as markers of hypercoagulability and chronic inflammation in patients with T2DM.…”
mentioning
confidence: 99%
“…However, the associations and interactions between inflammation and hemostasis have not been fully established in T2DM, although a causal link between the 2 systems has been suggested. 8 In our study, we sought to compare plasma biomarkers of inflammation and coagulation in patients with T2DM who do not have complications and patients with T2DM who have microvascular complications. Also, we aimed to explore the associations between inflammatory markers, coagulation and fibrinolysis parameters, and microvascular complications in patients with T2DM.…”
mentioning
confidence: 99%